Analisis Pemahaman Konsep Ekonomi Di Kalangan Siswa Sekolah Dasar - Hutasuhut, Saidun; Siagian, Irma; Safitri, Laila; Azzahra, Nabila; Ramadhani, Nabila Rizki; Lubis, Nazia Safira (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to analyze the understanding of basic economic concepts among people fourth grade students at SD Negeri 101801, especially regarding demand, supply and price. The research method used is descriptive qualitative through observation, interviews, and analysis of learning documents. The research results show that students have good understanding of the concept of price because of its relevance to everyday life day. However, understanding of the concept of demand and supply is still limited. Most students understand demand as a desire to buy, but not yet able to relate it to price factors critically. Meanwhile, in the offer concept, Students have difficulty understanding the relationship between price and quantity of goods offered. This research highlights the importance of more interactive economic learning and contextual to increase students’ understanding of economic concepts base.